REPRESENTATION OF THE NUMBER IN THE NUMBER SYSTEM OF 10 AS SUM OF THE LEVELS OF 3. - Ghafforov Husayn Aliyarovich; Jurayev Ilhom Ruzibayevich (Лучшие интеллектуальные исследования, 2024)
Annotation: This article examines the proof that arbitrary numbers in the 10-digit number system can be expressed as powers of 3.